2003
DOI: 10.1002/ajmg.a.20214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fragile X status categories and FMRP deficits on cognitive profiles estimated by robust pedigree analysis

Abstract: The effect of the fragile X pre-mutation and full mutation categories, and FMRP deficits in these categories, on neurocognitive status, have been assessed in fragile X individuals from 144 extended families, which included fragile X individuals, as well as their non-fragile X relatives. Neuropsychological status was assessed by the Wechsler summary and subtest test scores. A modification of the maximum likelihood estimators for pedigree data that is resistant to outliers was used to analyze the data. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 57 publications
4
39
1
Order By: Relevance
“…Arithmetic skill was also the only phenotypic measure that showed a highly significant relationship with methylation of the exonic units (see Table 2 in the online Data Supplement). Some earlier studies found arithmetic skills to be impaired in FM females, even in the absence of other cognitive impairments (38,39 ). Consistent with these data, we found that even in high-functioning FM females (FSIQ, VIQ, and PIQ values Ͼ70), analysis of CpG unit 10 -12 can identify individuals with specific impairments in arithmetic skills.…”
Section: Discussionsupporting
confidence: 90%
“…Arithmetic skill was also the only phenotypic measure that showed a highly significant relationship with methylation of the exonic units (see Table 2 in the online Data Supplement). Some earlier studies found arithmetic skills to be impaired in FM females, even in the absence of other cognitive impairments (38,39 ). Consistent with these data, we found that even in high-functioning FM females (FSIQ, VIQ, and PIQ values Ͼ70), analysis of CpG unit 10 -12 can identify individuals with specific impairments in arithmetic skills.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast with consistent reports on correlations between magnitude of FMRP decrease and severity of physical and cognitive phenotype [53,144], lymphocytic FMRP levels do not seem to predict behavioral abnormalities in FXS [145]. Initial studies demonstrated a modest relationship between FMRP deficit and severity of autistic behavior [13,146]; however, subsequent studies showed that after controlling for IQ the relationship vanishes [41,147]. Negative findings are not surprising considering that FMRP is an RNA-binding protein that regulates the synthesis, particularly at synaptic sites, of a relatively large number of proteins (5–8% total mRNA) [143,148,149].…”
Section: Genetic and Molecular Bases Of Asd In Fxs: Initial Insights mentioning
confidence: 48%
“…In most cases, the mutation consists of an unstable expansion of a CGG trinucleotide repeat within the 5 0 UTR region of FMR1, which when it reaches the 200-2,000 repeats range (vs. 5-40 normal), termed full mutation, leads to hypermethylation and silencing of the gene. In general terms, severity of FMRP deficit is correlated with severity of physical and neurobehavioral phenotype [Hagerman et al, 1994;Kaufmann and Reiss, 1999;Loesch et al, 2003]. Despite this, FMRP levels only account for a small proportion of the variance in different specific aspects of A neurobehavioral development and have virtually no influence on the severity of autistic behavior in FraX [Bailey et al, 2001a,b;Kaufmann et al, 2003a].…”
Section: Introductionmentioning
confidence: 99%